Perception of Philippine army enlisted personnel on their security of tenure: basis for policy review and reassessment - Bulauan-Bautista Pa, Folren (Parañaque City: Olivarez College, 2022)
The present study is comprehended with a goal of determining the perception of Philippine Army enlisted personnel on their security of tenure. Likewise, it aims to propose policy as an output of the study which she believes could greatly contribute for the welfare and development of the whole PA organization. The researcher utilized Quantitative Descriptive research design as this method provides quantitative responses which will be based on the information to be collected from the Enlisted Personnel and the Commissioned Officers groups. In particular, their responses to the numeric survey questions will be used to explore, identify, and critically analyze implications of aspects related to security of tenure of the military respondents in pursuant to Republic Act 6656. A total of 380 enlisted personnel and 20 commissioned officers will be the respondents of the study. A sample size of 195 enlisted personnel or 51.32 % and 19 commissioned officers or 95% are generated, through the use of Slovin's formula with 0.05 margin of error or with 95% level of significance. The total sample respondents of 214 or 54% of the total population of 400 will participate in the study.
Master Thesis
Keywords: Enlisted personnel; Attrition; Security of Tenure